INFLUENCE OF THE METABOLIC DRUGS ON THE ENDOTHELIAL FUNCTION OF PATIENTS WITH STABLE ANGINA III FC AND HYPERTENSION - Зозуляк, Н. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Combination of Coronary Artery disease and Hypertension is very common, that’s why an extremely important is the search of the treatment optimization of these patients to reduce complications, disability of the population and fatal consequences. Usually the treatment of comorbid pathology is focused on hemodynamic part of the cardiovascular system, but such drugs do not protect endothelium. The aim of the study was to increase effectiveness of treatment of the patients with Stable Angina with Hypertension by improvement of endothelial function on the background of therapy with basic drug and metabolic drugs mexicor, or tivortin, or combination of both. Material and methods. It was observed 125 patients with Stable Angina FC III and Hypertension. The effectiveness of the treatment was assessed by the dynamics of CAVI, endothelium-dependent vasodilatation, levels of total NO, endothelin-1 and malonic aldehyde. The results and conclusions. The result of the study showed that the most effective according to the improvement of endothelial function was combined use of mexicor and tivortin on the background of basic therapy. The results allow to recommend mexicor and tivortin as a means of basic therapy.